I tweet, therefore I am: a systematic review on social media use and disorders of the social brain - Nancy Yang; Bernard Crespi (BMC Psychiatry)
Abstract With rapid technological advances, social media has become an everyday form of human social interactions. For the first time in evolutionary history, people can now interact in virtual spaces where temporal, spatial, and embodied cues are decoupled from one another. What implications do these recent changes have for socio-cognitive phenotypes and mental disorders? We have conducted a systematic review on the relationships between social media use and mental disorders involving the social brain. The main findings indicate evidence of increased social media usage in individuals with psychotic spectrum phenotypes and especially among individuals with disorders characterized by alterations in the basic self, most notably narcissism, body dysmorphism, and eating disorders. These findings can be understood in the context of a new conceptual model, referred to here as ‘Delusion Amplification by Social Media’, whereby this suite of disorders and symptoms centrally involves forms of mentalistic delusions, linked with altered perception and perpetuation of distorted manifestations of the self, that are enabled and exacerbated by social media. In particular, an underdeveloped and incoherent sense of self, in conjunction with ‘real life’ social isolation that inhibits identify formation and facilitates virtual social interactions, may lead to use of social media to generate and maintain a more or less delusional sense of self identity. The delusions involved may be mental (as in narcissism and erotomania), or somatic (as in body dysmorphic disorder and eating disorders, encompassing either the entire body or specific body parts). In each case, the virtual nature of social media facilitates the delusionality because the self is defined and bolstered in this highly mentalistic environment, where real-life exposure of the delusion can be largely avoided. Current evidence also suggests that increased social media usage, via its disembodied and isolative nature, may be associated with psychotic spectrum phenotypes, especially delusionality, by the decoupling of inter and intra-corporeal cues integral to shared reality testing, leading to the blurring of self-other boundaries.